Incidence of injuries in Brazilian sailors of different technical levels Incidência de lesões em velejadores Brasileiros de diferentes níveis técnicos - Ruschel C.* (2009)
The first step to reduce the incidence of injuries in athletes is to assess the characteristics of occurrence, providing background for the structure and application of prevention programs. This study had the aim to investigate the incidence of injuries in sailing athletes of different technical levels. The sample was composed of 172 sailors, divided in three groups: 89 beginners, participants in the Optimist qualifying of the World Championship (group 1); 29 juvenile sailors, participants in the Youth Sailing Cup (group 2) and 54 national elite sailors, participants in the Pre-Olympic Sailing Week (group 3). The data collection instrument was a mixed questionnaire and the data were analyzed by descriptive statistics. Five athletes from group 1 (5.6%); five athletes from group 2 (17.2%) and 15 athletes from group 3 (27.8%) reported some kind of injury related with the modality. Higher incidence of injury was observed in the back and knee and the most reported diagnostic was muscular injury, followed by cuts, sprains and tendinitis. The incidence in sailing is low if compared with other sport modalities, despite the high physical demand required during the actions on the boat. It was verified that the professional athletes, who had higher age mean and time of practice, suffered the most injuries. On the other hand, the lowest incidence was among children and adolescents. Therefore, it is important that prevention programs start from the first years of practice in order to reduce the risk to future outbreaks, especially of chronic nature. Based on this information concerning kinds of injury, we suggest inclusion of exercises specific to musculature conditioning and compensation in the training programs, as well as stretching and relaxation sessions.